2017
DOI: 10.1016/j.electacta.2017.03.137
|View full text |Cite
|
Sign up to set email alerts
|

In situ and operando observation of surface oxides during oxygen evolution reaction on copper

Abstract: Formation and dissolution of oxide on copper under transpassive conditions, i.e. during OER and transpassive dissolution, in alkaline electrolyte was investigated by a combination of electrochemical techniques and in situ and operando Raman and photoluminescence (PL) spectroscopy, as well as spectropscopic ellipsometry. Experiments were conducted under potentiodynamic and potentiostatic polarisation in 0.1M NaOH.In chronoamperometry experiments with steps between potentials, oxide thickness continued increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
(128 reference statements)
1
29
0
1
Order By: Relevance
“…During OER, the metal oxide radicals considered as the catalytic intermediates for O À Ob ond formation are formed at the oxide/electrolyte interface. [16,[64][65][66][67][68] Thus,c hanges of valence state during OER monitored by in situ XAS may reflect these transition metal oxide radicals.However,XAS is abulk sensitive technique,soonly an average valence state of…”
Section: In Situ X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…During OER, the metal oxide radicals considered as the catalytic intermediates for O À Ob ond formation are formed at the oxide/electrolyte interface. [16,[64][65][66][67][68] Thus,c hanges of valence state during OER monitored by in situ XAS may reflect these transition metal oxide radicals.However,XAS is abulk sensitive technique,soonly an average valence state of…”
Section: In Situ X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…In former studies our group successfully employed in situ spectroscopic ellipsometry (SE) to probe metal supported oxide layer thicknesses simultaneously with spectral changes that can be attributed to composition changes in electrochemical setups. [24][25][26] It was shown that passive oxide films forming on Cu dissolve because of single charge oxygen vacancy formation during the OER. 25 In situ and operando measurements on metallic Cu showed that metastable Cu 4 O 3 forms before the oxide dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…In comparable works in NaOH, 17,53 no peak at ≈300 cm −1 was observed. Phosphate peaks around 1000 cm −1 are were not observed in the presence of this peak.…”
Section: Resultsmentioning
confidence: 67%
“…3) is qualitatively different from the ones obtained in alkaline environment. 17,53 Fig. 3a shows absorption spectra obtained during a CV experiment.…”
Section: Resultsmentioning
confidence: 99%